Pengaruh Firm Generated Content dan Persepsi Kualitas Produk Terhadap Keputusan Pembelian Pakaian Thrift pada Thriftshop Elnassupply - Muhammad Anas Mu’tashim; Indra Hastuti; Khabib Alia Akhmad (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
One of the current clothing phenomena that is popular with all groups is wearing used clothes that are still suitable for use or commonly called thrifting. In addition to product quality, the content produced by the company is an important element in encouraging consumers to make purchasing decisions. This study aims to analyze the influence of firm generated content and perception of product quality on purchasing decisions for thrift clothing. The population in this study were consumers of the elnassupply thriftshop. The sample in this study amounted to 64 respondents using purposive sampling techniques with criteria for the last 3 months. The data used in this study were primary data. The data collection method used was a questionnaire. The data analysis technique used was Structural Equation Modeling-Partial Least Square (SEM PLS) and using SmartPLS 4.0. The results of this study indicate that firm generated content has a positive and significant effect on purchasing decision, perceptions of product quality have a positive and significant effect on purchasing decisions..